Heat transfer in MHD flow of Carreau ternary-hybrid nanofluid over a curved surface stretched exponentially - Nabwey, Hossam A.; Rashad, A. M.; Khan, Waqar A.; El-Kabeir, S. M. M.; AbdElnaem, Shereen (Frontiers in Physics, 2023)
This investigation aims to study the MHD two-dimensional incompressible boundary layer performing non-Newtonian Carreau ternary-hybrid nanofluid flow with heat transfer through an exponential stretching curved surface.The ternary-hybrid nanofluid has been synthesized with titanium oxide, aluminum oxide, and silver dispersionin the base fluid water.TheNavier Stokes equation and Carreau ternary-hybrid nanofluid model govern the partial differential equations (PDEs), and appropriate similarity transformations are utilized to transfer these PDEs into ordinary differential equations (ODEs).The effects of the pertinent parameters on the dimensionless velocity and temperature profiles are analyzed with the aid of figures. This study provides new insights and solutions to previously unsolved problems related to heat transfer in the MHD flow of a Carreau Ternary-Hybrid Nanofluid over a curved surface stretched exponentially, or it could contribute to the existing knowledge and literature by refining existing models or methods.The surface drag force and Nusselt numbers are studied for the different values of the governing parameters throughgraphs.It is demonstrated that the heat transfer rate and skin friction increase from base fluid to mono, hybrid, and ternary nanofluids. Both heat transfer rate and skin friction increase with the addition of nanoparticles.